Preparing accounting graduates for digital revolution: A critical review of information technology competencies and skills development - PAN, Gary (Institutional Knowledge at Singapore Management University, 2016)
The pervasiveness of information technology (IT) in businesses has altered the nature and economies of accounting activities. In particular, the emergence of cloud computing, eXtensible Business Reporting Language, and business analytics in recent years have transformed the way companies report financial performance and make business decisions. As a consequence, there is a surge in demand for advanced IT skills among accounting professionals. In this research, we aim to review selected articles published between 2004 and 2014 based on selected search phrases. The outcome of the review may serve as an important input for current and future accounting curriculum revisions.